Dacie and Lewis Practical Haematollogy - Bain, Barbara J; Bates, Imelda; Laffan, Michael A (British : Elsevier, 2017)
Suitable for any haematology laboratory, this title covers all of the techniques used in the investigation of patients with blood disorders, including the advanced technologies as well as the tried and true manual methods of measurement.
Keywords: Sang -- Analyse; Hématologie -- Technique